Collective Bargaining and Public Benefit Conferral: A Jurisprudential Critique - Dion, Gérard (Relations industrielles / Industrial Relations, 1977)
This article reviews "Collective Bargaining and Public Benefit Conferral: A Jurisprudential Critique" by Robert S. Summers.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z